ANALYSIS OF STUDENTS' ABILITY TO UNDERSTAND THE MATHEMATICS CONCEPT IN THE APPLICATION OF MATLAB ASSISTED DISCOVERY LEARNING MODEL - SANTI MARIA SIMARMATA; Bornok Sinaga; HERMAWAN SYAHPUTRA (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
This study aims to describe: (1) The level of students' ability to understand mathematical concepts in the application of the Matlab-assisted Discovery Learning model; (2) The difficulty of students' understanding of mathematical concepts. in the application of the Matlab-assisted Discovery Learning model. This research is a qualitative research with a descriptive approach. Based on the research data, it was found that: (1) The level of ability to understand mathematical concepts of students in the application of the Matlab-assisted Discovery Learning model with good abilities had the highest percentage of 57% followed by excellent abilities students with a percentage of 24%, students with moderately capable with a percentage of 14 % and students with less ability with a percentage of 5%; (2) The difficulty in understanding students' mathematical concepts in the application of the Matlab-assisted Discovery Learning model is the difficulty of facts because it does not able to interpret the results obtained, unable to change the problem in a simpler model.